A COMPARATIVE REVIEW OF ARTIFICIAL LIFT METHODS - Ponomarenko O. S. (НТУ «ДП», 2024)
In the petroleum industry, artificial lift methods are crucial for enhancing oil recovery, especially as natural reservoir pressure declines. The main objective of artificial lift is to reduce the pressure in the wellbore, facilitating the flow of hydrocarbons to the surface. This review highlights the main artificial lift methods, emphasizing their operational principles, advantages, and limitations.
Keywords: artificial lift methods